2017
DOI: 10.1177/1010428317706215
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-124 suppresses proliferation and glycolysis in non–small cell lung cancer cells by targeting AKT–GLUT1/HKII

Abstract: Non-small cell lung cancer accounts for 85% of all types of lung cancer and is the leading cause of worldwide cancerassociated mortalities. MiR-124 is epigenetically silenced in various types of cancer and plays important roles in tumor development and progression. MiR-124 was also significantly downregulated in non-small cell lung cancer patients. Glycolysis has been considered as a feature of cancer cells; hypoxia-inducible factor 1-alpha/beta and Akt are key enzymes in the regulation of glycolysis and energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 23 publications
(29 reference statements)
5
54
0
Order By: Relevance
“…Specifically, downregulated miR-124 expression was identified in several types of cancer,16, 17, 18 and studies have shown that the overexpression of miR-124 suppresses cancer progression by inhibiting the Akt pathway,14, 17 which suggests that miR-124 may play a general role in the regulation of the Akt pathway in different types of cancer. The downregulated expression of miR-124 in lung cancer tissues 19 and the negative correlation between miR-124 and p-Akt in lung cancer cells 20 have been previously reported. However, the detailed mechanism by which miR-124 regulates Akt phosphorylation is not clear in NSCLC cells.…”
Section: Introductionsupporting
confidence: 52%
“…Specifically, downregulated miR-124 expression was identified in several types of cancer,16, 17, 18 and studies have shown that the overexpression of miR-124 suppresses cancer progression by inhibiting the Akt pathway,14, 17 which suggests that miR-124 may play a general role in the regulation of the Akt pathway in different types of cancer. The downregulated expression of miR-124 in lung cancer tissues 19 and the negative correlation between miR-124 and p-Akt in lung cancer cells 20 have been previously reported. However, the detailed mechanism by which miR-124 regulates Akt phosphorylation is not clear in NSCLC cells.…”
Section: Introductionsupporting
confidence: 52%
“…MiRNAs have been associated with the initiation and progression of NSCLC (31)(32)(33). As such, a comprehensive understanding of the association between dysregulated miRNA expression and NSCLC may contribute to the identification of novel therapeutic methods for patients with this disease.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs/miRs) are a class of small RNAs that serve essential functions in various physiological and pathological processes (3)(4)(5). A large body of evidence has demonstrated that the dysregulation of miRNA expression has been identified in a number of different types of cancer (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%